2010
DOI: 10.1161/hypertensionaha.110.158139
|View full text |Cite
|
Sign up to set email alerts
|

Effects on Peripheral and Central Blood Pressure of Cocoa With Natural or High-Dose Theobromine

Abstract: Abstract-Flavanol-rich cocoa products have been reported to lower blood pressure. It has been suggested that theobromine is partially responsible for this effect. We tested whether consumption of flavanol-rich cocoa drinks with natural or added theobromine could lower peripheral and central blood pressure. In a double-blind, placebo-controlled 3-period crossover trial we assigned 42 healthy individuals (age 62Ϯ4.5 years; 32 men) with office blood pressure of 130 to 159 mm Hg/85 to 99 mm Hg and low added cardio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(61 citation statements)
references
References 39 publications
0
57
1
3
Order By: Relevance
“…This fact is very important from a health perspective because caffeine acts as a stimulant and vasoconstrictor, whereas theobromine acts as a vasodilator and lowers blood pressure. Furthermore, theobromine acts as a muscle relaxant and diuretic (Van den Bogaard et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This fact is very important from a health perspective because caffeine acts as a stimulant and vasoconstrictor, whereas theobromine acts as a vasodilator and lowers blood pressure. Furthermore, theobromine acts as a muscle relaxant and diuretic (Van den Bogaard et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…This is of interest, as additional mechanisms of action of cocoa flavanol appear to exist (eg, via modulation of the reninangiotensin system), 37 and other cocoa constituents such as theobromine and caffeine may also contribute partly to the observed changes in FMD and wave reflections. One study of theobromine from dark chocolate, however, found no hemodynamic or electrophysiological effects in young adults 38 ; another found the caffeine and theobromine content of flavanolpoor chocolate were similar to that of flavanol-rich chocolate, although only dark chocolate affected vascular function and NO bioavailability, 39 and van den Bogaard et al 40 reported naturaldose theobromine cocoa did not significantly change either 24-hour ambulatory or central SBP compared with placebo.…”
Section: 2425mentioning
confidence: 99%
“…The other aspect is the effect of methylxantines in human body, since caffeine is well known for its action in central nervous system promoting a stimulating effect, increasing the sense of allarm, vitality, psychomotor reactions and rising the blood pressure. Dn the other hand, theobromine has no stimulating effect, because the action of theobromine in the central nervous system is very weak or almost non-existent, but it can act as a vasodilator, a muscle relaxant, diuretic and blood pressure reducer (Van den Bogaard et al, 2010;Mitchell et al, 2011).…”
Section: Phenolic Compounds and Methylxantinesfrom Fermented And Driementioning
confidence: 99%
“…While caffeine has a stimulating effect on the brain, increasing the psychomotor reactions and blood pressure, the theobromine acts as a muscle relaxant, diuretic and blood pressure reducer (Van den Bogaard et al, 2010;Bruinsma & Taren, 1999).…”
Section: Introductionmentioning
confidence: 99%